Reestructuración técnico-administrativa en la empresa Dos Publicidad S.A.S. en la ciudad de Bogotá D.C. (2018)
In the present work, the technical administrative restructuring for the company Dos Publicidad S.A.S. in order to know the current status and propose improvement actions in order to make their processes more productive. It began with the realization of a diagnosis of the company, thus determining its current situation, it used tools within which was the business self-diagnosis established by the Chamber of Commerce of Bogotá, then a PESTAL analysis was conducted and the Matrix was developed DOFA, in this way the internal-external panorama of the company was known. A technical study was carried out based on the finished product as it is worth mentioning that Dos Publicidad is a company that uses outsourcing for the manufacture of its products in which a time standardization was elaborated, by means of an Operations Diagram and in turn a diagram of process flow which showed the time of manufacture of the product that was studied, then a design was made of a new distribution in plant in which distances traveled and manufacturing times were reduced, the necessary conditions to perform the operations were also established through an ergonomic and anthropometric study and all those improvements required in the company's production plant. Finally, an administrative study was prepared in which the strategic planning of the company was evaluated and the corresponding updates, organizational structure and salary study were calculated, calculating the payroll and their respective projections. Concluding the technical and administrative study.